Penerapan Metode Belajar Kooperatif Tipe Think Pair Share (TPS) untuk Meningkatkan Motivasi Belajar Peserta Didik - Ermayulis, Syafni (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This study aims to describe the planning, implementation and evaluation of increasing the learning motivation of students in class X IPS 3 MAN 1 Pekanbaru for the 2022/2023 academic year using the TPS (Think Pair Share) method. This research is a classroom action research (CAR) and the data is presented through qualitative and quantitative descriptive data. The learning motivation of class X IPS 3 students is still low, researchers are trying to increase it by applying the TPS type cooperative method. This research was conducted in two cycles. Each cycle consists of 4 stages, namely: planning, implementation, action, observation and reflection. The subjects of this study were 34 class X IPS 3 students for the 2022/2023 academic year. The results showed that learning motivation was 71% in cycle 1, 80% in cycle 2. There was an increase of 9% of students who were motivated, became active, both physically, mentally and socially in the learning process